2006
DOI: 10.1039/b600721j
|View full text |Cite
|
Sign up to set email alerts
|

The temperature-dependence of rapid low temperature reactions: experiment, understanding and prediction

Abstract: Despite the success of the CRESU (Cinétique de Réaction en Ecoulement Supersonique Uniforme) method in measuring rate coefficients for neutral-neutral reactions of radicals down close to the very low temperatures prevalent in dense interstellar clouds (ISCs), there are still many reactions of potential importance in the chemistry of these objects for which there have been no measurements of low temperature rate coefficients. One important class of reactions is that between atomic and molecular free radicals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 90 publications
8
109
0
1
Order By: Relevance
“…[1][2][3][4][5][6] In addition, both ethanol and OH have been detected in interstellar molecular clouds and star forming regions (hot and cold cores) such as W3(OH) and Sgr B2, where temperatures can reach as low as 40 K. [7][8][9][10][11][12][13] Millar et al 12 suggested that ethanol could potentially be used as a chemical clock for hot cores if the kinetics of its reactions with species including the hydroxyl radical were better understood at temperatures pertinent to such environments. Conducting kinetic studies with species known to be present in these cold environments is important for the advancement of chemical models of these regions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In addition, both ethanol and OH have been detected in interstellar molecular clouds and star forming regions (hot and cold cores) such as W3(OH) and Sgr B2, where temperatures can reach as low as 40 K. [7][8][9][10][11][12][13] Millar et al 12 suggested that ethanol could potentially be used as a chemical clock for hot cores if the kinetics of its reactions with species including the hydroxyl radical were better understood at temperatures pertinent to such environments. Conducting kinetic studies with species known to be present in these cold environments is important for the advancement of chemical models of these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Because kinetic experiments 35 and our electronic structure calculations suggest that the reaction of dicarbon with acetylene …”
Section: Center-of-mass Functionsmentioning
confidence: 99%
“…However, the chemical databases or networks used to model such environments contain a relatively small number of this class of reaction [2]. Those reactions that have been studied at relevant low temperatures (< 200 K) already occur quickly at room temperature, with k 298K > 10 -11 molecule -1 cm 3 s -1 [3][4], and do not possess any significant barrier to reaction. In this paper, we show that despite the presence of an energy barrier, the reaction between OH and methanol proceeds to products rapidly at very low temperatures, which we interpret via a mechanism involving the formation of a weak hydrogen bonded association adduct, and quantum mechanical tunnelling, as shown schematically in Figure 1.…”
mentioning
confidence: 99%
“…However, closer inspection of Figure 2 reveals that the Arrhenius plot is curved, with the apparent activation barrier to reaction decreasing as temperature is lowered. Deviation from Arrhenius behaviour is not uncommon and it is often explained by the reaction not proceeding via a single-step, involving a weakly bound intermediate [4], or due to the presence of quantum mechanical tunnelling (QMT) [6].…”
mentioning
confidence: 99%